The flourishing teacher : vocational renewal for a sacred profession - Lake, Christina Bieber (IVP Academic, an imprint of InterVarsity Press, 2020)
"Drawing on more than twenty years of teaching experience, Christina Bieber Lake helps you rediscover your passion for the teaching profession. Creatively structured around the typical rhythms of the academic calendar, this book offers refreshing and practiced advice about how to flourish in the midst of the teaching life"--